Knowledge Spillovers in Regional Innovation Systems A Case Study of CEE Regions (Advances in Spatial Science, The Regional Science Series,, 2018)
This book provides an assessment of the evolution and dynamics of regional innovation systems (RISs) and the economic and social impact of resulting knowledge spillovers, presenting comparative case studies on the regions of several Central and Eastern European (CEE) countries (Czech Republic, Poland, Hungary, Slovakia, Lithuania and Estonia). It analyses RISs on the basis of several dimensions, such as absorption capacity and intellectual capital, and using several methods such as data envelopment analysis, patent network analysis, and weighted sum approach. Further, by looking at the economic and social impact of knowledge spillovers in RISs and networking, it identifies key distinguishing factors, including foreign direct investments, still prevalent centralized decision-making, EU-driven innovation policies and public financing of innovations. Sectoral case studies, e.g. from the automobile, chemical and other hi-tech manufacturing industries, are presented to help readers understand the different types of knowledge spillovers in CEE countries and the evolution and dynamics of RISs, and provide a multifaceted overview of the CEE regions.